Polysemy in Justin Bieber's Song Lyrics - Rafislam Dilapanga; Indri Wirahmi Bay; Jefriyanto Saud (Jambura Journal of English Teaching and Literature, 2022)
This research aimed to discover the types of polysemy words to determine the meaning of polysemy words in twelve Justin Bieber’s song lyrics. The qualitative-descriptive method was used in this research. The data were collected by downloading the lyrics, reading and understanding the lyrics, and note-taking. The researchers used the theory of Miles and Huberman (1994) to determine the steps of analyzing data. The theory of Asher (2011) was used to classify and analyze the polysemy word into types of polysemy which were accidental polysemy (unrelated meaning) and logical polysemy (related meaning). Furthermore, the theory of Haspelmath (2001) was used to classify and analyze the word classes of polysemy words. As a result, the researchers found 20 polysemy words which were 10 words classified into accidental polysemy, and 10 words classified into logical polysemy. Those polysemy words were mostly in abstract nouns. Lastly, this research was expected to provide valuable information about polysemy for other researchers who would take polysemy as the topic of the research.